(untitled) (Journal of Patan Academy of Health Sciences, 2021)
Introduction: Children present with different renal diseases with variations according to different geographic locations. This study aims to determine the trend of pediatric renal disease presenting. Method: This retrospective study from pediatric nephrology clinic register during 2008 to May 2018 at Patan Hospital, Patan Academy of Health Sciences, Nepal to analyze the changing pattern of renal disease. The prevalence and characteristic of renal diseases were compared between the 1st and 2nd 5-y period, the age at presentation and gender was analyzed. Mean age at presentation was analyzed by independent t-test, a p-value <0.05 was considered significant. The study was approved by the ethical committee. Result: A total of 352 children visited the nephrology clinic, male:female ratio 1.42:1, mean age 6.25±4.5 y, the majority in 0-5 y. Congenital anomalies of the kidney and urinary tracts (CAKUT) were 39%, mostly vesicoureteral reflux. Acute glomerulonephritis and the nephrotic syndrome were seen in 32.7% and 23.6%. Children <5 y of age presented with CAKUT while ≥5 y with acute glomerulonephritis. The mean age at presentation for CAKUT was 2.9±3 y and acquired diseases 8.46±3.91 y, p-value<0.05; and for glomerulonephritis 9.8±2.91 y and nephrotic syndrome 6.91±4.08 y, p-value<0.05. Conclusion: There was a decrease in the number of children visiting the nephrology clinic. Children <5 y presented with CAKUT while ≥5 y had acquired conditions. Children with acute glomerulonephritis were of a higher age than children with nephrotic syndrome.